Hubungan Kecerdasan Linguistik dengan Kemampuan Berbahasa Peserta Didik di SMA Negeri 15 Kota Pekanbaru - Sukenti, Desi (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2017)
The purpose of this study is to determine the significant relationship of Linguistic Intelligence with Language Ability Students class X in SMA Negeri 15 Kota Pekanbaru. The research problem encountered in this study is the low ability of the students to speak in SMA Negeri 15 Pekanbaru. The method used is correlation method (Arikunto, 2010). The population is all the students of class X which amounts to 180 people. The sample used amounted to 80 people as research data. Data collection techniques used are questionnaires. The data is analyzed by using Statistical Analysis Version 20. The results of research on the relationship of linguistic intelligence with the language skills of class X students in SMA Negeri 15 Kota Pekanbaru. Validity and reliability test results obtained 0.882> 0.6 and 0.903> 0.6 This means the instrument used reliable. The conclusion that Pearson Product Moment correlation coefficient between two variables are linguistic intelligence variable (X) and language ability variable (Y). The obtained probability value Sig (2-tailed) is smaller than 0.05 ie 0,000 <0.05, then Ho is rejected. This means that there is a significant relationship between linguistic intelligence with the language skills of learners. So the relationship between linguistic intelligence with language skills of class X students in SMA Negeri 8 Pekanbaru is 0.790. This correlation value can be interpreted with strong relationship level criteria.